The Role of HR Analytics in Enhancing Organizational Agility: A Theoretical Exploration and Empirical Evidence (The Journal of Theoretical Accounting Research, 2025)
Organizational agility has become a critical capability for sustaining competitiveness in rapidly changing environments. This study explores the role of human resource analytics in enhancing agility by theorizing how data-driven insights transform human resource practices into strategic enablers of adaptability. Drawing on dynamic capabilities theory, the resource-based view, and strategic human resource management perspectives, the research develops a conceptual model that positions human resource analytics at the core of sensing, seizing, and reconfiguring processes. A conceptual and theory-building design was adopted rather than an empirical approach, integrating insights from prior scholarship to construct a refined framework. The results reveal that human resource analytics strengthens sensing capability by predicting workforce shifts, improves seizing capability through evidence-based decision-making, and enhances reconfiguring capability by supporting flexible redeployment and continuous reskilling. The framework further identifies leadership support and ethical governance as critical moderators that shape the extent of these relationships. Five theoretically grounded propositions summarize these linkages and provide a roadmap for empirical validation. The study contributes by repositioning human resource analytics from an operational tool to a strategic capability, highlighting the importance of contextual enablers, and offering guidance for both scholars and practitioners seeking to advance organizational adaptability in dynamic environments.